A Study of Organizational Culture in the Context of the Ethnometric Approach - E M Gudzenko (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2012)
The article describes the current areas of research in the field of national particular features and cross-cultural distinctions in the framework of the ethnometric approach. The author analyzes the following conceptions: G. Hofstede's cultural dimensions theory, F. Trompenaars' method of studying the cross-cultural interaction and types of organizational culture. Special attention is given to the World Values Survey project initiated by R. Inglehart and devoted to studying cultural particular features in different countries.